A FIELD RESEARCH ON RELATIONSHIP BETWEEN ALCOHOLIC DRINKINGS, DRUGS AND CRIME - Kürşad ŞAHİNLİ and Mehmet Ali TEKİNER (International Journal of Eurasia Social Sciences, 2018)
The aim of this study is looking for answers of is there relationship between alcohol and drug abuse with criminal activity and what are the effects, dimensions and types of this relationship. The data used in this study were taken from the unpublished PhD thesis of Şahinli (2016). The research was conducted between December 2014 and January 2015. Sample group of study was 346 prisoners, and population group was 4220 prisoners. Thus, this study was conducted with 97,5 % confidence level. In the sample group, 274 (79,8 %) of the prisoners were male while 70 (20,2 %) were women. The prisoners’ ages vary between 18 and 70 years and the average age were 35. Face to face method was used with prisoners who were in prisons of Ankara. Surveys were fulfilled to prisoners in their wards of prisons. In the study, five hypotheses were identified to examine the relationship between alcohol and drug use and criminal behavior. These hypotheses are based on the psychopharmacological model and the economic model which included in Goldstein’s (1985) triple model. It is concluded that drugs are more related to crime in terms of economic model and using alcohol is more related to crime in terms of psychopharmacological model. According to another result of the study is alcohol is more related to violent behavior than to other drugs.